Pemanfaatan Artificial Neural Network Terhadap Klasifikasi Penyakit Tanaman Padi Menggunakan Citra Daun - Sunandar, Nandi; Sutopo, Joko (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
Rice is a type of plant that is very essential for humans. Rice is used as a staple food by a large portion of people, especially in Asia. Therefore, proper care and management of rice plants are crucial to maximize crop yields and meet the food needs in Indonesia, particularly for the staple diet. One of the common factors that hinder rice production is diseases that affect rice plants. If left untreated, it can have a detrimental impact on the much-needed rice production in Indonesia. Some common rice diseases include Bacterial Leaf Blight, Brown Spot, and Leaf Smut. Hence, early detection is required as a preventive measure against these diseases. One way to address this issue is by applying artificial intelligence, where AI can play a significant role in disease identification in rice plants. This allows farmers to take clear actions in disease management. Identification is performed using leaf images and an Artificial Neural Network (ANN) algorithm with an accuracy of 83%.